First record of anomalous otoliths of Menticirrhus americanus in the South Atlantic - Maichak de Carvalho, Barbara (2019)
Sagitta otoliths are usually formed of calcium carbonate polymorphs as aragonite. The objective of this study was to verify which carbonate polymorph is predominant in the sagitta otolith of Menticirrhus americanus and check whether this pattern remains in otoliths with morphological alterations. Otoliths of M. americanus were obtained from five sites on the southeast-south coast of Brazil (São Sebastião (SS) 23°45′S–45°24′O, n = 29; Cananéia-Iguape Estuarine Complex (CI) 25°02′S–47°54′O, n = 30; Paranaguá Estuarine Complex (PEC) 25°28′S–48°20′O, n = 35; Itapoá (IT) 26°07′S–48°36′O, n = 31; Laguna (LA) 28°28′S–48°46′O, n = 13). The characterization of carbonate polymorphs of otoliths was performed through Raman spectroscopy, a photonic and non-destructive technique that analyzes molecular vibrations induced by laser. We analyzed 138 pairs of M. americanus otoliths, of which eight otoliths from different pairs presented morphological alterations (SS n = 1, CEP n = 5, IT n = 1, LA n = 1). The Raman spectra show that normal otoliths, that is, without morphological alterations, presented only aragonite in their structure. Among the otoliths that presented morphological alterations, the Raman spectra allowed to identify in six otoliths the deposition of aragonite and in only two otoliths the deposition of vaterite (one specimen of the PEC and one of SS).